(untitled) (ABDIMAS: Jurnal Pengabdian Masyarakat, 2024)
Coconut sugar production is one of the leading commodities in Kabupaten Banyumas that has great potential to improve the regional economy. However, the coconut sugar production process in Pernasidi Village, especially at the Gendis Asri Farmer Group, faces several issues related to work safety and food safety. This community service program aims to increase farmers’ awareness and efficacy of work safety and food safety in the coconut sugar production process. The methods used include the provision of Personal Protective Equipment (PPE), occupational risk management training, and food safety training based on Hazard Analysis Critical Control Points (HACCP) principles. The results of the program showed an increase in farmers’ knowledge and awareness of work safety and food safety. In addition, the replacement of production equipment with stainless steel pans successfully reduced metal contamination in coconut sugar products. Overall, this program has had a positive impact on improving the quality and safety of coconut sugar products, which is expected to improve the welfare of farmers in Pernasidi Village.